EVALUATION OF IMPACT OF CONTINUOUS EPIDURAL ANESTHESIA OF LOWER EXTREMITIES ON MUSCLE STRENGTH AFTER TOTAL ENDOPROSTHESIS REPLACEMENT OF THE KNEE JOINT - R. V. Garyaev; I. A. Rychkov (Вестник анестезиологии и реаниматологии)
A prospective, randomized, controlled study included investigation of data of 45 oncology patients who had total endoprosthesis replacement of the knee joint. The control group (n=23) had the continuous block of peripheral nerves for pain relief, and the trial group (n=22) had continuous epidural anesthesia. With the help of mechanic dynamometer the strength of maximum voluntary isometric muscle contraction by flexion and extension of healthy leg in the knee joint was measured in the early postoperative period. Given the continuous epidural analgesia compared with the control group the maximum difference in the muscle strength of lower extremity was observed in the evening on the day of surgery and it made 37% by the knee joint flexion (7.3 ± 6.1 against 11.6 ± 3.2 kgs ∙ m, p = 0.0065, 95% CI 1.2–7.4) and 41% by extension (9.9 ± 8.8 against 16.9 ± 4.9 kgs ∙ m, p = 0.0023, 95% CI 2.6–11.4). On the 1st and 3rd days after the surgery the muscle strength was not statistically different compared to the control group, but it was lower that the preferred level by 14-8%, p < 0.05; in 5–27 patients the reduction of muscle strength was more than 20% of the one in the preoperative period.